EMPOWERING ENGINEERING STUDENTS THROUGH OPEN-SOURCE 3D PRINTING - May Alashwal,; Mohammed Algarni, (PEOPLE: International Journal of Social Sciences, 2025)
This paper explores how open-source 3-D printing enhances engineering skills, education, and professional development. Originally dominated by proprietary systems, 3-D printing has been democratized by open-source platforms like the RepRap project and Prusa i3, which allow engineers to rapidly prototype, experiment with materials, and collaborate. These platforms advance innovation by providing access to affordable tools, encouraging creativity and problem-solving. The paper examines how universities have integrated 3-D printing into their curricula, offering students practical, hands-on experience in design, manufacturing, and interdisciplinary projects. This shift bridges the gap between theoretical knowledge and real-world application, preparing students for careers in industries such as aerospace, healthcare, and automotive. Professionally, open-source 3-D printing offers engineers ongoing opportunities to update their skills and remain competitive. Despite challenges like quality control and scalability, technology continues to evolve, driven by collaborative innovation. Open-source 3-D printing is expected to play a pivotal role in advancing engineering by enabling complex designs, cost-effective manufacturing, and novel applications across various industries.